Comparison of the influence of the type of acidic environment on the properties of acid-resistant alkali-activated cements - Zozulynets, Viktoriia; Kovalchuk, Oleksandr (Transfer of innovative technologies, 2023)
The article is devoted to the study of acid resistance of materials developed on the basis of hybrid alkali-activated cements and includes the results obtained during previous studies focused in this direction. This directly concerns the composite compositions of the received cements. The relevance of the research is ensured by the need of the world market of building materials for modern, effective materials that will retain high acid resistance indicators along with increased physical, mechanical and technological characteristics. After all, as is known, traditional acid-resistant cements based on liquid potassium and sodium glass, although they provide appropriate values of resistance to the influence of an acidic environment, are extremely sensitive to the influence of water, which greatly reduces their service life. And materials based on Portland cement are generally not characterized by acid resistance due to the high content of portlandite (Ca(OH)2), highly basic calcium hydrosilicates and ettringite in the structure of hardened cement stone. That is why alkali-activated systems were chosen as the basis, the experience of working with them confirms the effectiveness of their use in the development of this research area. In the course of this study, a comparative characterization of the influence of the type of aggressive environment on the processes of structure formation of cement stone and the formation of acid-resistant phases is conducted. 5% solutions of hydrochloric (HCl) and nitric (HNO3) acids were used for the study. The obtained results not only confirm the possibility of using such cements in the conditions of an aggressive environment with a low pH, but also reflect the degree and influence of this type of environment on the material made according to the presented compositions. Thus, the compressive strength of the samples made according to these tested compositions after 90 days of exposure in hydrochloric and nitric acid solutions ranges from 43.1 MPa to 45.7 MPa and from 47.1 MPa to 49.7 MPa, respectively.